2006
DOI: 10.1161/01.str.0000206442.86238.39
|View full text |Cite
|
Sign up to set email alerts
|

α-Galactosidase A Deficiency Leads to Increased Tissue Fibrin Deposition and Thrombosis in Mice Homozygous for the Factor V Leiden Mutation

Abstract: Background— Factor V Leiden (FVL) is a common genetic risk factor for vascular thrombosis in humans. Fabry disease, an X-linked lysosomal storage disorder attributable to α-galactosidase A (GLA) deficiency, is associated with premature vascular events that may be thrombotic in nature. Methods and Results— To examine a potential interaction between FvL and Gla defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…77,78 By quantitating fibrin deposition and intravascular thrombosis, we have found that the factor V Leiden mouse has also been useful to elucidate prothrombotic phenotypes in mice that develop age-related vascular disease. 52,59,79 In addition, Bodary et al observed a significant increase in thrombotic tendency with age and fatness in mice of the KK/HlJ strain. 52 Gender differences related to thrombosis have not been well documented in animal models to date, but there are clear gender effects in partial thromboplastin time, prothrombin 80 Based on these data, it is probable that there are gender effects on thrombosis in several mouse strains.…”
Section: Westrick Et Al Murine Models Of Vascular Thrombosis 2087mentioning
confidence: 99%
“…77,78 By quantitating fibrin deposition and intravascular thrombosis, we have found that the factor V Leiden mouse has also been useful to elucidate prothrombotic phenotypes in mice that develop age-related vascular disease. 52,59,79 In addition, Bodary et al observed a significant increase in thrombotic tendency with age and fatness in mice of the KK/HlJ strain. 52 Gender differences related to thrombosis have not been well documented in animal models to date, but there are clear gender effects in partial thromboplastin time, prothrombin 80 Based on these data, it is probable that there are gender effects on thrombosis in several mouse strains.…”
Section: Westrick Et Al Murine Models Of Vascular Thrombosis 2087mentioning
confidence: 99%
“…To date, previous studies have demonstrated Gb3 accumulation in both vascular smooth muscle (VSM) and endothelium in the vasculature of Gla‐knockout (Gla −/0 ) mice, 7,8 a murine model for Fabry disease 9 . The increased vascular accumulation of Gb3 has been associated with an increased propensity for thrombosis, 7,10 as well as increased atherogenesis, 11 both of which are associated with endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Histological evidence suggests many similarities with human Fabry disease, although some discordance is present (4,(11)(12)(13). One significant advantage of the murine model is the ability to investigate Fabry tissues such as the aorta and heart, which are generally inaccessible in clinical studies.…”
mentioning
confidence: 99%